Cost-analysis of universal decolonization with pure hypochlorous acid and mupirocin to reduce MRSA infections in intensive care burn unit patients - Mallow, Peter J.; Chakravarthy, Debashish; Foster, Kevin (Frontiers in Pharmacology, 2025)
IntroductionBurn patients are at high risk for infections, particularly Methicillin-resistant Staphylococcus aureus (MRSA). Universal decolonization strategies have demonstrated effectiveness in reducing infection rates. This study aimed to evaluate the cost implications of using pure hypochlorous acid (pHA) and mupirocin to prevent MRSA infections in hospitalized burn patients.MethodsA patient-level microsimulation model was developed to perform a cost analysis from the US health system perspective. Clinical inputs were derived from a retrospective observational study. The primary outcome was the reduction in MRSA infections per 1,000 bed days. Cost estimates, expressed in 2023 US dollars, were gathered through a pragmatic literature review of publicly available sources. Deterministic and probabilistic sensitivity analyses were conducted to assess the robustness of the findings.ResultsBefore the introduction of pHA, burn patients were 3.05 times more likely to develop MRSA infections. The estimated cost of treating MRSA infections was 224,376 per 1,000 bed days in the pre-pHA period, compared to 148,812 in the post-pHA period. After including the cost of pHA, the net savings amounted to 75,564 per 1,000 bed days, or 75.56 per bed day. Sensitivity analyses confirmed the robustness of these results across a range of input values.ConclusionThe combination of pHA and mupirocin appears to be a cost-saving strategy for reducing MRSA infections among hospitalized burn patients.